Considerando : A = a3-2a2+3 e B= a3-2a2-a+5, temos que A-B é igual a :
A)a-2
B) -a+8
C)4a2-a+8
D)2a3-4a2-a+8
Soluções para a tarefa
Respondido por
19
A-B=
![( {a}^{3} - {2a}^{2} + 3) - ( {a}^{3} - {2a}^{2} - a + 5) = \\ {a}^{3} - {2a}^{2} + 3 - {a}^{3} - {2a}^{2} - a + 5 = \\ = {a}^{3} - {a}^{3} - {2a}^{2} - {2a}^{2} - a + 3 + 5 = \\ = { - 4}^{2} - a + 8 ( {a}^{3} - {2a}^{2} + 3) - ( {a}^{3} - {2a}^{2} - a + 5) = \\ {a}^{3} - {2a}^{2} + 3 - {a}^{3} - {2a}^{2} - a + 5 = \\ = {a}^{3} - {a}^{3} - {2a}^{2} - {2a}^{2} - a + 3 + 5 = \\ = { - 4}^{2} - a + 8](https://tex.z-dn.net/?f=%28+%7Ba%7D%5E%7B3%7D+-+%7B2a%7D%5E%7B2%7D+%2B+3%29+-+%28+%7Ba%7D%5E%7B3%7D+-+%7B2a%7D%5E%7B2%7D+-+a+%2B+5%29+%3D+%5C%5C+%7Ba%7D%5E%7B3%7D+-+%7B2a%7D%5E%7B2%7D+%2B+3+-+%7Ba%7D%5E%7B3%7D+-+%7B2a%7D%5E%7B2%7D+-+a+%2B+5+%3D+%5C%5C+%3D+%7Ba%7D%5E%7B3%7D+-+%7Ba%7D%5E%7B3%7D+-+%7B2a%7D%5E%7B2%7D+-+%7B2a%7D%5E%7B2%7D+-+a+%2B+3+%2B+5+%3D+%5C%5C+%3D+%7B+-+4%7D%5E%7B2%7D+-+a+%2B+8)
logo, R.:c)
logo, R.:c)
Jeniffer14Souza:
Obrigada
Perguntas interessantes